2013
DOI: 10.1002/jgrd.50180
|View full text |Cite
|
Sign up to set email alerts
|

Transport effects on the vertical distribution of tropospheric ozone over the tropical marine regions surrounding India

Abstract: [1] The measurements of vertical distribution of ozone have been made over the Bay of Bengal and the Arabian Sea in spring 2006 during a cruise campaign, namely, the Integrated Campaign for Aerosol, Gases and Radiation Budget. The average tropospheric columnar ozone (TCO) values are found to be 36.1 AE 6.9 Dobson unit (DU) and 41.7 AE 5.0 DU over the Bay of Bengal and the Arabian Sea, respectively. In contrast to TCO, ozone mixing ratios are higher by about 10 ppbv in the lower 3 km over the Bay of Bengal due … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 38 publications
2
27
0
Order By: Relevance
“…It is established in the previous studies that LRT plays an important role in the AS pre-monsoon ozone pool (Lal and Lawrence, 2001;Chand et al, 2003;Srivastava et al, 2011Srivastava et al, , 2012Lal et al, 2013Lal et al, , 2014. Trajectory models are used to investigate the LRT pathways of the air parcels.…”
Section: Long-range Transport Mechanism and Pollutant Accumulationmentioning
confidence: 99%
See 1 more Smart Citation
“…It is established in the previous studies that LRT plays an important role in the AS pre-monsoon ozone pool (Lal and Lawrence, 2001;Chand et al, 2003;Srivastava et al, 2011Srivastava et al, , 2012Lal et al, 2013Lal et al, , 2014. Trajectory models are used to investigate the LRT pathways of the air parcels.…”
Section: Long-range Transport Mechanism and Pollutant Accumulationmentioning
confidence: 99%
“…In previous studies using the ozonesonde measurements above the west coast of India and the data from two campaigns 1999 INDian Ocean EXperiment (INDOEX) campaigns and the Integrated Campaign for Aerosols, Gases and Radiation Budget (ICARB) campaign, which was conducted during March-May 2006), the higher AS TOC during pre-monsoon season was confirmed to be significantly influenced by LRT of the continental anthropogenically influenced outflows from the Middle East, western India, Africa, North America and Europe (Lal and Lawrence, 2001;Chand et al, 2003;Srivastava et al, 2011Srivastava et al, , 2012Lal et al, 2013Lal et al, , 2014. In addition, by comparing the INDOEX ozone measurements from both sides (northern and southern) of the ITCZ (Intertropical Convergence Zone), the influence of the ITCZ functioning as a sink for ozone was determined by the observed 4 times higher TOC values on the northern side of AS compared to the southern side (Chand et al, 2003).…”
Section: Introductionmentioning
confidence: 97%
“…Although validation of the ozone profile product (mostly earlier versions) has been partially performed against aircraft, ozonesonde, and microwave limb sounder (MLS) data, these evaluations are limited to certain time periods and/or spatial region and/or to only portion of the product (e.g., OC or TOC only) (Bak et al, 2013a;Hayashida et al, 2015;Lal et al, 2013;Liu et al, 2010a, b;Pittman et al, 2009;Sellitto et al, 2011;Wang et al, 2011;Yang et al, 2007;Ziemke et al, 2014). Additionally, the quality of ozone profile retrievals is very sensitive to the signal-to-noise ratio (SNR) of the radiance measurements as well as their radiometric calibration, which may degrade over time as shown in GOME and GOME-2 retrievals (Cai et al, 2012;Liu et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Most of the studies based on in situ measurements have, however, been confined to the southern part of India (e.g. Mandal et al, 1998;Sinha et al, 2016) and the adjacent marine regions (Lal et al, 2013). Ganguly and Tzanis (2011) used ozone-sonde observations from three Indian stations operated by the Indian Meteorological Department (IMD) and suggested that overall STT only plays a minor role in the budget of tropospheric ozone over India.…”
Section: Introductionmentioning
confidence: 99%